(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: Neonatal intestinal obstruction due to jejunoileal atresia is not uncommon. Recommended treatment is resection with end to back anastomosis and post operative care in Neonatal Intensive Care Unit (NICU) with Total Parenteral Nutrition (TPN) support. In a setup without NICU and TPN, mortality of primary anastomosis is very high due to unusual delay in starting enteral feeding. Bishop Koop technique seems to allow early oral feeding and rapid establishment of normal gastrointestinal function and thus reduce mortality and morbidity. Objective: To find out the outcome of Bishop Koop procedure in patients with Jejunoileal atresia. Methods: This is an ongoing study started from March, 2011 in the Department of Pediatric Surgery, Chittagong Medical College Hospital. Here we are presenting our initial experience till June, 2012 (duration of 16 months). During this period total 13 patients of uncomplicated Jejunoileal atresia was treated surgically. Four patients were treated by classical end to oblique anastomosis and all died. Rest of the 9 patients were treated by Bishop Koop technique. Overall outcome of this technique was assessed considering time to establish oral feeding and normal bowel movement, ceasation of coming distal stomas effluent, weight gain, death etc. Result: Out of 9 patients, 6 patients weighing less than 2.5 Kg. Type- III A was the commonest variant. Two patients died following surgery due to sepsis. Oral feeding was possible within 4-7 postoperative day in all survived patients except one. In follow up satisfactory weight gain was observed in all those patients. Conclusion: Bishop Koop technique could be considered as preferred surgical option in a set up without NICU and TPN. J. Paediatr. Surg. Bangladesh 3(1): 5-11, 2012 (January)